Laser ring structures in step-index fibers. Issue 1 (1st September 2022) - Slavchev, V; Dakova, A; Gocheva, N; Bozhikoliev, I; Kovachev, K; Biswas, A
Abstract: The formation and propagation of optical ring structures, given by a system of amplitude equations for the components of the electric field is investigated. The calculations are made in approximation of second-order linear dispersion and self-phase modulation. New class analytical solutions, characterizing the generation and evolution of laser ring structures in optical waveguides with step-index profile and anomalous dispersion, are described in the present work. The stability of these optical formations is a result of the specific combination of nonlinearity, diffraction and angular distribution. Laser vortices have an amplitude type of singularity which appears as depolarization of the vector field in the light radiation spot.